Opportunity to Build Maine’s Workforce amid the COVID-19 Pandemic - Fairman, Laura (Maine Policy Review, 2021)
Author Laura Fairman argues that state policymakers should reconsider their economic development strategy in light of remote work trends. Implementing a grant-making initiative to attract new residents would add to the tools currently targeted at strengthening and growing Maine’s workforce.
Keywords: remote work; population decline